TSL082: Introductory Literature I / Centre of Foundation Studies - UiTM, Centre of Foundation Studies (2023)
This course introduces the students to two genres of literature – poetry and fiction (short story and the novel). It aims to provide a sound basis for the appreciation of literature, promote close study and analysis of literary texts and enhance writing skills useful in academic settings Through the genre-based approach, students will have to identify and demonstrate their understanding by applying the literary elements to a wide array of genres orally and in written work which are fundamental for further literary study.